PENINGKATAN HASIL BELAJAR IPAS MELALUI METODE PEMBELAJARAN BERBASIS SIMULASI PADA MURID KELAS V SD NEGERI 03 PONTIANAK KOTA - Imaculata Kiding, Theresa; Trigasari, Salamah; Hidayanah, Fesa; Nurrahim, Cantika; Sholihah, Dzakiyyah; Triwiro S, Paskalis; Ghozali, Imam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research was motivated by the low IPAS learning outcomes of fifth-grade students at SD Negeri 03 in Pontianak Kota, which were caused by the predominance of conventional, teacher-centered instruction. This study aimed to improve students’ IPAS learning outcomes through the implementation of a simulation-based Problem-Based Learning (PBL) model. The research method used was collaborative Classroom Action Research (CAR) based on the Kemmis & McTaggart model, conducted in two cycles. The research subjects consisted of 29 students. Data were collected using test techniques (multiple-choice evaluation questions) and non-test techniques (observation sheets), then analyzed using quantitative and qualitative descriptive methods. The results showed that in the pre-cycle phase, the class average was only 67.24, with a classical mastery rate of 37.93% (11 students achieved mastery). After implementing the intervention in Cycle I, the class average increased to 76.38 with a classical mastery rate of 68.97% (20 students met the criteria) and an N-Gain value of 0.28 (low category). In Cycle II, there was a significant jump in results, with the class average reaching 85.17, the percentage of students meeting the standard reaching 89.66% (26 students met the standard), and the N-Gain value rising to 0.37 (moderate category). Cumulatively, the improvement from the pre-cycle to Cycle II resulted in a total N-Gain index of 0.55 (moderate category). The success indicator targets were optimally met, leading to the conclusion that the implementation of a simulation-based PBL model is effective in improving elementary school students’ IPAS learning outcomes.